2023
DOI: 10.1007/s10914-023-09650-y
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the land-to-sea transition in carnivorans from the evolution of sacrum morphology in pinnipeds

Abstract: The form and function of the sacrum are of great relevance to understand the evolution of locomotion in tetrapods because it is a key piece of the vertebrate skeleton. The sacrum connects the caudal and presacral regions of the vertebral column and the hindlimbs through the pelvis. Here, we investigate sacrum shape evolution in pinnipeds (Carnivora: Pinnipedia) in relation to terrestrial mammalian carnivorans (fissipeds), and we include crown and stem taxa to quantify the morphological changes they experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…Therefore, we hypothesize that A. kelloggi employed a mixed type of locomotion, or that the thrust would not be produced entirely from the lumbar region. Instead, only the first lumbar vertebra was likely involved in exerting propulsive forces and a recent study revealed that the sacrum of Allodesmus was more like that of phocids than to that of otariids [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we hypothesize that A. kelloggi employed a mixed type of locomotion, or that the thrust would not be produced entirely from the lumbar region. Instead, only the first lumbar vertebra was likely involved in exerting propulsive forces and a recent study revealed that the sacrum of Allodesmus was more like that of phocids than to that of otariids [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also hypothesize that the axial evolution in phocids is subject to greater constraints compared to otariids, because the phocid vertebral column exhibit a rigid anterior region and a highly mobile posterior region, whereas otariids have evolved to maintain maximum flexibility in the entire vertebral column [72]. All vertebrae of phocids, particularly the thoracics and lumbars, are more disparate than the ones of otariids, which probably relates to the role of the vertebral column in swimming, and probably increases morphological variability among different regions depending upon its role in locomotion, such as providing rigidity (the case of posterior thoracics) or mobility (the case of the lumbars).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tail length itself is associated with substrate, with arboreal mammals tending to maintain longer tails and tail loss generally occurring in terrestrial species [ 124 ]. Recently, the shape of the sacrum has been quantified using GMM in relation to the swimming strategies in extant pinnipeds [ 125 ]. The pinniped sacrum is characterized by a set of traits indicative of the low stresses it withstands because of the reduced time pinnipeds spent on land compared to terrestrial carnivorans.…”
Section: Overview Of Carnivoran Ecomorphologymentioning
confidence: 99%